Oxidative Stability and Sensory Properties of Pecan Nuts - Descalzo, Adriana Maria (2022)
Pecans are the nut with the higher oil content. In addition, they present a large number of polyunsaturated fatty acids, which are susceptible to oxidation. Oxidative damage in pecans is traduced in lower quality aspects, appearance of rancidity and acidity, loss of sweetness and firmness, darker kernels, and darker shells. The use of different strategies for the conservation of entire and shelled nuts is discussed in terms of oxidation and the consequences on nuts quality.